2010
DOI: 10.1007/978-3-642-12654-3_25
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Brain Decoded Signals for Online User Adaptive Gesture Recognition Systems

Abstract: Activity and context recognition in pervasive and wearable computing ought to continuously adapt to changes typical of open-ended scenarios, such as changing users, sensor characteristics, user expectations, or user motor patterns due to learning or aging. System performance inherently relates to the user's perception of the system behavior. Thus, the user should be guiding the adaptation process. This should be automatic, transparent, and unconscious. We capitalize on advances in electroencephalography (EEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…We showed principles that allows one sensor node to autonomously learn how to recognize user activity from another one, thus allowing an activity recognition system to autonomously expand to new resources discovered or introduced in the environment, without user intervention [23]. We showed that adaptive methods can lead to an autonomous system capable of self-improvement, by using minimalist or even unconscious user feedback [24].…”
Section: Context Recognition In Opportunistic Sensor Configurationsmentioning
confidence: 99%
“…We showed principles that allows one sensor node to autonomously learn how to recognize user activity from another one, thus allowing an activity recognition system to autonomously expand to new resources discovered or introduced in the environment, without user intervention [23]. We showed that adaptive methods can lead to an autonomous system capable of self-improvement, by using minimalist or even unconscious user feedback [24].…”
Section: Context Recognition In Opportunistic Sensor Configurationsmentioning
confidence: 99%
“…This data was used offline to assess EEG-based adaptation of gesture recognition systems. More details about the experimental setup can be found in [8] B. Experimental protocol Seven healthy male subjects aged 25 to 47 took part in the the experiment.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…In particular, we assume that a subject independent gesture classifier has been previously obtained and the EEG decoding signals will be used to adapt this classifier to a specific new user. Accordingly, trials that not classified as errors would signal that the last gesture was correctly recognized, it can thus be used as an example to further train the current classifier in a supervised manner [8].…”
Section: Eeg Based Adaptation Of Activity Recognitionmentioning
confidence: 99%
“…One way to detect a fault in action is to compare the sensor values resulting from the action with those expected after a success. Experimental evidence has shown that humans employ this strategy to detect failure of predicted actions (Förster et al 2010). Another way is to build compliant behaviours, as we did for grasping resources (see Sect.…”
Section: On Robustnessmentioning
confidence: 99%